Perbandingan Setiap Kontur Transfomasi Pada Anomali Magnetik Untuk Identifikasi Sesar (Studi Kasus : Sesar Toru Pada Great Sumatera Fault) - Simanjuntak, Andrean Vesalius Hasiholan; Jihad, Abdi (Lambung Mangkurat University Press, 2017)
Toru fault is one part of the Great Sumatran Fault, which is actively moving every year. These activities cause severe damage and cause fatalities too, therefore the best step is to know and identify the fault. From there, we can learn how to mitigate before and after the earthquake. For that reason, the geophysical method is the right step to do, because the results can describe the surface and subsurface state of a region. Geomagnetic method is one of the geophysical methods that can explain the subsurface conditions in an area. This method is based on the difference of positive and negative closures, which indicates the presence of two poles, and an indication of the existence of a different layer. The data in this study were obtained from the data of CHAMP Satellite, which measures field to the distance between grid to another grid is 3.8 km. The method which used for this research is transformation techniques on magnetic field anomalies. From there, we will know the difference characteristics of each transformation. The results show that each graph on the transformation to the pole, which is given 4 lines, follows the movement of the fracture. The graph on the first line has an anomalous range of -20 nT - 80 nT. In the second line, the range of anomalies obtained ranges from -50 nT - 250 nT. On the third line, the range of anomalies obtained is about -250 nT - 150 nT. On the fourth line, the anomaly range obtained is -200 nT - 200 nT.